Centrality in Workers' Belief Systems About Unions - Langford, Tom (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1993)
In this article it is contended that the centrality (or salience) of beliefs is an important but overlooked feature of belief Systems about unions. This theme is pursued through a study of the centrality of beliefs about unions in a sample of Hamilton, Ontario workers. Each participant sorted 48 separate statements about unions, identifying those statements with which she/he most agreed and most disagreed. These data are analyzed in two distinct ways. First, the article outlines general tendencies in the centrality of belief s for the entire sample. However, people differ in what they think is most important about unions. Therefore, the article also identifies the central belief s for six typical ways of thinking about unions.